Implications of Marriage Agreements on the Status of Couples' Property on Money Laundering Criminal Acts in Indonesia - Kurniawan, Alan; Asri, Dyah Permata Budi; Markoni; Kanthika, I Made (International Journal of Science and Society, 2025)
This study examines the implications of prenuptial agreements on the status of marital property in Money Laundering Crimes (TPPU). The research aims to analyze the legal status of assets separated through prenuptial agreements when one spouse is involved in money laundering, and to evaluate legal protection mechanisms for good-faith spouses. The study focuses on the conflict between the principle of party autonomy in marriage law and the principles of follow the money and asset recovery under the Anti-Money Laundering Act. The method used is normative juridical, employing statutory and theoretical approaches, including the theory of legal protection, the theory of evidence, and the concept of reverse burden of proof. Findings reveal that prenuptial agreements hold a strategic role as instruments of legal certainty under the principle of freedom of contract and the 1945 Constitution. However, in practice, within money laundering and corruption cases, their effectiveness is limited because the principles of follow the money and reverse burden of proof grant broad authority to law enforcement to seize assets even if formally legitimate. The normative conflict between civil and criminal law creates legal uncertainty disadvantaging third parties, while existing protections remain suboptimal due to high evidentiary standards and procedural barriers. Thus, regulatory harmonization is necessary to ensure legal certainty, prevent misuse of prenuptial agreements, and provide effective protection for good-faith spouses.